Examining the Development of a Social Media Strategy for a National Sport Organisation A Case Study of Tennis New Zealand - Ashleigh-Jane Thompson; Andrew J. Martin; Sarah Gee; Andrea N. Eagleman (Journal of Applied Sports Management, 2014)
The application of technology and the rise in social media has not gone unnoticed in sports and has become a vital tool for sport marketers as sport consumers’ media consumption grows. This paper offers an analysis on the development and maintenance of a social media strategy for a National Sport Organisation (NSO) in New Zealand. This initiative, implemented for Tennis New Zealand (TNZ) in 2010, was conducted to provide a minority sport (in terms of mainstream media) with its first online social media presence. This study involved a qualitative and quantitative analysis of Tennis New Zealand’s (TNZ) development and maintenance of a social media strategy through fieldwork, social media metrics data collection and analysis, and evaluation, and highlights a number of issues in the development and effective utilisation of social media for an NSO. In particular applying a ‘one size fits all’ approach to its management despite the uniqueness of the sport product. Creative online strategies using technologies such as Facebook must be employed, monitored and evaluated to ensure they continue to meet the needs and expectations of all stakeholders. Such strategies include the use of promotions, ‘behind-the-scenes’ material, and constant engagement and conversation with fans and followers.
Keywords: social media; national sport organisations; online communities; marketing